Compliance with a high-protein and energy-dense oral nutritional supplement in patients with disease-related malnutrition: a randomized open-label crossover trial - Leon-Sanz, Miguel; Linares, Francisca; Gonzalo, Montserrat; Tapia, María José; Maiz-Jimenez, María; Ruiz Aguado, Marta; Lizán, Luis; Olveira, Gabriel (Frontiers in Nutrition, 2023)
Introduction: Patient compliance with oral nutritional supplements (ONS) is not optimal for meeting energy and nutritional requirements in a high proportion of patients with disease-related malnutrition (DRM). Energy density or prescribed volume of ONS may impact compliance. Methods: A randomized, open-label crossover trial was conducted in outpatients with DRM to compare compliance with a high energy-dense ONS (edONS, 2.4kcal/ml) and a reference ONS (heONS, 2.0kcal/ml) (NCT05609006). Patients were randomly assigned to two eight-week treatment sequences of four-weeks periods: edONS+heONS (sequence A) or heONS+edONS (sequence B). Patients daily reported the amount of product left over, gastrointestinal tolerance and satisfaction with ONS. A non-inferiority analysis was performed to compare the compliance rate (percentage of consumed energy over the prescribed) for each period and sequence. Results: Fifty-three patients were assigned to sequence A and 50 to sequence B, (55.7±13.9 years, 37.0% female, 67.1% oncology patients). In sequence A, the compliance rates were 88.6±14.3% vs 84.1±21.8% (p=0.183), while in sequence B, they were 78.9±23.8% vs 84.4±21.4% (p<0.01). In both sequences, the lower range of the confidence interval for compliance with edONS was greater than the non-inferiority threshold (for sequence A ΔCompA was 4.5% [95% CI, −2.0 to 10.0%], and for sequence, B ΔCompB was 5.6% [95% CI, −3.0 to 14.0%]). The total discarded cost for each ONS was higher for heONS than edONS, being the difference statistically significant in sequence B. BMI increased slightly and not significantly in both sequences, and the percentage of patients with severe malnutrition was reduced. The frequency of gastrointestinal symptoms was low for both sequences, and satisfaction with ONS was slightly higher for edONS. Conclusions: Our findings highlight that edONS was non-inferior to heONS in terms of consumed energy over the prescribed, with a lower amount of edONS discarded, which suggests a higher efficiency of edONS.